Pengaruh Faktor Sosial, Ekonomi Dan Lingkungan Terhadap Kejadian Tuberkulosis Paru Pada Anak Di Kota Jambi - Jalius; Arnalia Devi; Ummi Kalsum (Jurnal Pembangunan Berkelanjutan, 2020)
Tuberculosis is a disease cause by Mycobakterium tuberculosis in children occurs on 0 -14 years old children. The purpose of this study was to analyze the influence between the social, economic  and environment factors with the incidence of tuberculosis in children. This study design was case control. Examined variables were parental knowledge, birth weight, BCG immunization, house contact, smoking, parental income, ventilation, lighting, temperature, humidity and residential density was the incidence of pulmonary tuberculosis in children. Case samples were the total number of cases recorded in the TB-03 register in Jambi City, July - December 2019. Control was taken by means of the neighborhood, age and gender matching method. The number of samples was 104 people 1:1 (52 cases and 52 controls). Data collection by interview using a questionnaire, observation and measurement. Data analyzed with chi square test and binary logistic regression at 95% CI. Case characteristics in boys (61.5%) aged over 5 years. There was a influence between smoking, house contact, and bedroom lighting with the incidence of pulmonary tuberculosis in children. The social, economy and environment factors were not related to the incidence of pulmonary tuberculosis in children. The most dominant factor the incidence of tuberculosis in children is home contact with a probability of 99% supported by home lighting factors (OR = 7.35, 95% CI = 2.120 - 25.508) after being controlled by BCG immunization, smoking, bedroom temperature, house temperature and occupancy density. The research conclusion shows that Pulmonary Tuberculosis in children only happens when there is a direct contact from the grown ups who have the disease with the children and they live at the same house. This is also supported with the house lighting as the breaking factor of Mycobacterium Tuberculosis bacteria.